Gel polymer electrolyte and preparation method and application thereof
By using gel polymer electrolytes prepared with fluorine-containing monomers and nitrogen-containing crosslinking agents in lithium-ion batteries, the cycle life and safety problems of lithium-ion batteries under high current density are solved, and high energy density and long cycles are achieved Stability, suitable for fast charging and discharging applications.
Patent Information
- Application Number
- CN202411254606.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Lithium-ion batteries have a decreased cycle life under high current density, the risk of electrolyte leakage and combustion increases, and lithium ion migration is hindered, affecting energy density and safety.
Gel polymer electrolyte prepared with fluorine-containing monomers and nitrogen-containing crosslinking agents inhibit lithium dendrites and electrolyte leakage through the polymer frame structure, introduce NH-containing functional groups to promote lithium ion transmission, limit anion migration, and form high performance. gel electrolyte.
Improve the discharge specific capacity and cyclic stability of lithium-ion batteries under high current density, reduce the risk of electrolyte leakage, enhance the chemical stability and safety of the battery, and is suitable for fast charging and discharging applications.
Smart Images

Figure CN119230930A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery electrolytes, and in particular relates to a gel polymer electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries provide high-performance energy storage solutions with excellent characteristics such as high energy density, safety and environmental protection. They are widely used in portable electronic devices, electric vehicles, renewable energy storage and other fields. In order to improve the energy density of batteries, researchers have developed many new electrode materials, such as nickel-cobalt-manganese oxide or nickel-cobalt-aluminum oxide positive electrode materials. However, the increase in energy density and voltage also intensifies the side reactions of the electrolyte on the positive electrode surface, further accelerating the destruction of the positive electrode particles, and ultimately leading to a decrease in the battery cycle life. In addition, the electrolyte decomposes on the negative electrode surface to form organic lithium salts, which hinder the migration of lithium ions at the interface. In addition, carbonate-based lithium-ion battery electrolytes have a low flash point, and there is a risk of leakage and combustion during the cycle, which leads to safety hazards in the battery.
[0003] Gel polymer electrolytes combine the advantages of solid and liquid electrolytes. The electrolyte is sealed in the polymer framework, reducing the safety hazard of electrolyte leakage. At the same time, the polymer skeleton structure can inhibit the growth of lithium dendrites. Compared with solid polymer electrolytes, lithium ions can migrate rapidly in the liquid phase, showing excellent properties, including high ionic conductivity, good interfacial properties and excellent chemical stability. With the increasing demand for batteries in society, fast charging capability has also become one of the criteria for measuring the practical application potential of batteries. However, compared with liquid electrolytes, due to the presence of polymers that hinder the migration of lithium ions to a certain extent, gel polymer electrolyte lithium-ion batteries are usually unable to exhibit high discharge specific capacity at high current density. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a gel polymer electrolyte and a preparation method and application thereof. The purpose of the present invention is to provide a gel polymer electrolyte used at high current density to further improve the in-situ polymerization interface stability and ion transmission rate.
[0005] The first aspect of the present invention is to provide a gel polymer that can be stably used under high current density. The polymer framework is polymerized by monomers, crosslinking agents and initiators. The monomers are fluorine-containing monomers, including one or two of trifluoroethyl acrylate (TFEA), 2,2,3,3-tetrafluoropropyl methacrylate (TFPMA), 1H,1H-perfluoropropyl methacrylate (PFPMA), hexafluorobutyl acrylate (HFBA), 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane (OFHDA) and 2-(perfluorohexyl)ethyl methacrylate (PFEMA). The crosslinking agent is a nitrogen-containing monomer, including one of N,N'-methylenebisacrylamide (MBA), hexamethylenebisacrylamide (HABA) and N,N'-vinylbisacrylamide (EBA).
[0006] The monomers and cross-linking agents are shown in structural formulas 1 to 9:
[0007]
[0008] The structural formula of the polymer framework is shown in Formula 10:
[0009]
[0010] In formula 10, R1 is a fluorinated ester group, R2 is -CH3 or -H, and R3 is an amide group.
[0011] For example, the combination of monomers and crosslinking agents can be a combination of trifluoroethyl acrylate and N,N'-methylenebisacrylamide, or a combination of 2-(perfluorohexyl)ethyl methacrylate and 2-(2,2-dimethyl-1,3-propylene)acrylate, but is not limited to the listed combinations, and other unlisted combinations within the monomer range are also applicable.
[0012] Furthermore, in the present invention, the lithium salt is selected from any one or a combination of at least two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, and lithium bis(trifluorosulfonyl)imide.
[0013] Furthermore, in the present invention, the initiator is any one of azobisisobutyronitrile, dicumyl peroxide, dibenzoyl peroxide or azobisisoheptylnitrile, and the added amount is 0.01 to 5 wt % of the mass of the polymer precursor.
[0014] Furthermore, in the present invention, the organic solvent is selected from any one of ethylene carbonate, diethyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and fluoroethylene carbonate, and any one or more of them are blended in any volume ratio.
[0015] Furthermore, in the present invention, the thermal initiation conditions are: the polymerization temperature is 50 to 80° C., and the polymerization time is 0.5 to 4 hours.
[0016] The second aspect of the present invention is to provide a method for preparing the above-mentioned gel polymer, wherein a precursor electrolyte containing a monomer, a cross-linking agent, an initiator, an organic solvent and a lithium salt is heated to react at a temperature of 50 to 80°C for 0.5 to 4 hours to transform the precursor electrolyte from a liquid state into a gel state to obtain a gel polymer electrolyte.
[0017] The third aspect of the present invention is to provide the use of the gel polymer in a lithium ion battery. The lithium ion battery comprises a positive electrode, a negative electrode, a separator and the gel polymer electrolyte.
[0018] Furthermore, in the gel polymer lithium ion battery provided by the present invention: the positive electrode is one of a nickel-cobalt-manganese ternary positive electrode, a nickel-cobalt-aluminum positive electrode, a lithium cobaltate positive electrode, and a lithium iron-manganese phosphate positive electrode; the negative electrode is one of a graphite negative electrode, a lithium titanate, a silicon-carbon negative electrode, and metallic lithium; and the diaphragm is one of a polypropylene diaphragm, a polyethylene diaphragm, a cellulose diaphragm, and a glass fiber diaphragm.
[0019] Furthermore, in the present invention, the positive electrode material includes positive electrode active material, conductive carbon black and binder, wherein the positive electrode active material accounts for 80-95% of the positive electrode material, the conductive carbon black accounts for 2.5-10% of the positive electrode material, and the binder accounts for 2.5-10% of the positive electrode material.
[0020] Furthermore, in the present invention, the negative electrode material includes a negative electrode active material, conductive carbon black, a binder and a thickener, wherein the negative electrode active material accounts for 90-96.5% of the negative electrode material, the conductive carbon black accounts for 1.5-3% of the negative electrode material, the binder accounts for 1.5-3% of the negative electrode material, and the thickener accounts for 1.5-3% of the negative electrode material.
[0021] Beneficial Effects
[0022] The present invention provides a polymer skeleton in formula 10, introduces NH-containing functional groups into the main chain, and uses fluorine-containing short chains as side groups. The present invention forms fluorine-containing functional groups on the polymer side chains in situ to interact with lithium ions and promote lithium ion transmission; while the NH-containing functional groups on the main chain limit the migration of anions and increase the number of ion migration. Therefore, the copolymerized fluorine-containing monomer and nitrogen-containing crosslinking agent gel polymer electrolyte in the present invention enables the battery to exhibit good discharge specific capacity and cycle stability at high current density. Therefore, the lithium ion battery based on the gel polymer electrolyte of the present invention has excellent performance at high current density, and is particularly suitable for application scenarios requiring fast charging and discharging, such as electric vehicles and high-power electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1It is the thermogravimetric analysis curve diagram of Example 1 and Comparative Example 1.
[0024] Figure 2 This is a graph showing the electrochemical window test analysis results of Example 1 and Comparative Example 1.
[0025] Figure 3 This is a graph showing the steady-state current method test results of Example 1.
[0026] Figure 4 This is a graph showing the steady-state current method test results for Comparative Example 1.
[0027] Figure 5 The charge and discharge voltage curves of the lithium batteries of Example 1 and Comparative Example 1 under long-term cycling.
[0028] Figure 6 The cycling performance diagram of the full battery of Example 1 and Comparative Example 1 at 3C, 25°C.
[0029] Figure 7 This is a scanning electron microscope (SEM) image of the positive electrode surface of the full battery of Example 1 after 400 cycles.
[0030] Figure 8 This is a scanning electron microscope (SEM) image of the positive electrode surface of the full battery of Comparative Example 1 after 400 cycles.
[0031] Fig. 9 This is a scanning electron microscope (SEM) image of the negative electrode surface of the full battery of Example 1 after 400 cycles.
[0032] Fig.10 This is a scanning electron microscope (SEM) image of the negative electrode surface of the full battery of Comparative Example 1 after 400 cycles. DETAILED DESCRIPTION
[0033] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0034] Example 1
[0035] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0036] Step 1: Add 0.025 g TFEA and 0.025 g MBA to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1 mol / L LiPF6, add 0.0015 g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0037] Step 2: Inject 30 μL of the precursor electrolyte into the button cell and assemble it in the glove box. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, let it stand at room temperature for 2 hours to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 75°C for 0.5 hours to obtain a gel polymer electrolyte.
[0038] Example 2
[0039] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0040] Step 1: Add 0.028g TFPMA and 0.025g MBA to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1mol / L LiPF6, add 0.0017g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0041] Step 2: Inject 30 μL of the precursor electrolyte into the button cell for assembly. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, let it stand at room temperature for 1 hour to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 75°C for 0.5 hours to obtain a gel polymer electrolyte.
[0042] Example 3
[0043] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0044] Step 1: Add 0.03 g PFPMA and 0.025 g MBA to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1 mol / L LiPF6, add 0.002 g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0045] Step 2: Inject 30 μL of the precursor electrolyte into the button cell for assembly. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, let it stand at room temperature for 1 hour to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 75°C for 0.5 hours to obtain a gel polymer electrolyte.
[0046] Example 4
[0047] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0048] Step 1: Add 0.034 g HFBA and 0.025 g N,N'-methylenebisacrylamide to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1 mol / L LiPF6, add 0.002 g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0049] Step 2: Inject 30 μL of the precursor electrolyte into the button cell for assembly. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, let it stand at room temperature for 1 hour to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 75°C for 0.5 hours to obtain a gel polymer electrolyte.
[0050] Example 5
[0051] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0052] Step 1: Add 0.038g OFHDA and 0.025g MBA to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1mol / L LiPF6, add 0.0022g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0053] Step 2: Inject 30 μL of the precursor electrolyte into the button cell for assembly. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, stand at room temperature for 4 hours to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 75°C for 0.5 hours to obtain a gel polymer electrolyte.
[0054] Example 6
[0055] This embodiment provides a gel polymer electrolyte lithium ion battery, which is prepared by the following steps:
[0056] Step 1: Add 0.043 g PFEMA and 0.025 g MBA amine to a lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1 mol / L LiPF6, add 0.0025 g initiator azobisisobutyronitrile and mix well to obtain a precursor electrolyte.
[0057] Step 2: Inject 30 μL of the precursor electrolyte into the button cell for assembly. The button cell specification is a CR2032 series battery. The size of the positive electrode used is a 15 mm NCM811 single-sided electrode, the negative electrode used is a graphite negative electrode with a diameter of 16 mm, and the diaphragm used is a polypropylene diaphragm with a diameter of 19 mm. After the assembly is completed, stand at room temperature for 2 hours to allow the electrolyte to fully infiltrate the diaphragm, and then polymerize at 70°C for 40 minutes to obtain a gel polymer electrolyte.
[0058] The preparation method of button lithium ion battery is as follows:
[0059] (1) Preparation of positive electrode: Single crystal LiNi 0.8 Co 0.1 Mn 0.1 The O2 ternary positive electrode material, conductive agent carbon black (Super-P) and binder (PVDF) were dissolved in N-methylpyrrolidone at a mass ratio of 8:1:1, mixed evenly to form a positive electrode slurry, and then the positive electrode slurry was evenly coated on the current collector aluminum foil, and finally dried at 80°C under vacuum conditions for 12 hours to form a positive electrode sheet for a lithium-ion battery;
[0060] (2) Preparation of negative electrode sheet: Graphite negative electrode material, conductive agent carbon black (Super-P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were dissolved in deionized water at a mass ratio of 95.5:1.5:1.5:1.5 and mixed evenly to form a negative electrode slurry. The negative electrode slurry was then evenly coated on the current collector copper foil, and finally dried at 80°C under vacuum conditions for 12 hours to prepare a negative electrode sheet for a lithium-ion battery.
[0061] (3) Assembly of lithium-ion batteries: Assembled in a glove box with an argon content of 99.999%, an actual oxygen content of <0.1ppm, and a moisture content of <0.1ppm; the battery is assembled in the order of positive electrode shell, positive electrode, precursor solution, diaphragm, precursor solution, negative electrode, gasket, spring and negative electrode shell.
[0062] Comparative Example 1
[0063] A lithium-ion battery electrolyte of EC / DEC / DMC (V:V:V=1:1:1) containing 1 mol / L LiPF6 was prepared, and 30 μL of the electrolyte was injected into a button cell for assembly. The button cell was a CR2032 series battery, the positive electrode used was a 15 mm NCM811 single-sided electrode piece, the negative electrode used was a graphite negative electrode with a diameter of 16 mm, and the separator used was a polypropylene separator with a diameter of 19 mm.
[0064] Comparative Example 2
[0065] A lithium-ion battery electrolyte of EC / EMC (V:V=3:7) containing 0.5 mol / L LiDFOB and 1 mol / L LiPF6 was prepared, and 30 μL of the electrolyte was injected into a button cell for assembly. The button cell specification was CR2032 series battery, the size of the positive electrode used was a 15 mm NCM811 single-sided electrode piece, the size of the negative electrode used was a graphite negative electrode with a diameter of 16 mm, and the size of the diaphragm used was a polypropylene diaphragm with a diameter of 19 mm.
[0066] The button cells made from the above-mentioned Examples 1 to 6, Comparative Examples 1 and 2 were subjected to electrochemical performance tests, including an electrochemical window test and a long cycle test (after 2 cycles of activation at 0.1C at room temperature, a long cycle test was performed at 3C, with a charge and discharge range of 2.7 to 4.5V). The specific test results are shown in Table 1.
[0067] Table 1
[0068]
[0069] The results show that Examples 1 to 6 have a higher electrochemical window and a higher first-cycle efficiency than Comparative Examples 1 and 2, indicating that the obtained gel polyelectrolyte has better electrochemical stability, and has a higher capacity retention rate after 100 cycles, indicating better long-cycle stability at high current density.
[0070] The thermogravimetric curves of the electrolytes of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, it is found that the comparative example 1 starts to lose weight rapidly from room temperature, while the example 1 starts to show obvious thermal weight loss at 130°C, indicating that the polymerized electrolyte has better thermal stability and anti-oxidative decomposition ability.
[0071] The electrochemical windows of Example 1 and Comparative Example 1 were tested. Figure 2 As shown, Comparative Example 1 begins to exhibit severe polarization at around 4.5 V, while Example 1 begins to polarize at around 5.0 V, indicating that the gel polymer electrolyte has higher electrochemical stability.
[0072] The electrochemical windows of Example 1 and Comparative Example 1 were tested. Figure 3 and Figure 4 As shown, the ion migration number of Example 1 is 0.67, while the ion migration number of Comparative Example 1 is 0.33, which indicates that the combination of the introduced fluorine-containing side chain and the main chain containing the NH functional group can effectively promote the migration of lithium ions and effectively limit the migration of anions.
[0073] Assemble the lithium battery, by Figure 5 It can be seen that at 0.2 mA cm -2 At the current density, Example 1 still did not show obvious polarization phenomenon after 1400 hours of cycling, while Comparative Example 1 began to show obvious increase in polarization voltage after 700 hours of cycling. This shows that the gel polymer electrolyte has better long-cycle stability.
[0074] The long cycle performance of the lithium ion batteries of Example 1 and Comparative Example 1 was tested. Figure 6 As shown. In Example 1, the initial discharge capacity of the battery at 3C is 145.8 mAh g -1 The capacity retention rate after 300 cycles is 73.2%. The initial discharge capacity of the battery in comparative example 1 at 3C is 148.9 mAh g -1 , the capacity retention rate after 300 cycles is 33.3%, which indicates that the gel polymer electrolyte has better long-term cycle stability at high current density.
[0075] The SEM images of the positive electrodes of the lithium ion batteries of Example 1 and Comparative Example 1 after 400 cycles are as follows: Figure 7 and Figure 8 As shown, it can be found that the positive electrode particles of Example 1 maintain a relatively complete morphology after cycling, while the positive electrode particles of Comparative Example 1 are more broken, which indicates that the integrity of the positive electrode can be effectively protected by in-situ polymerization.
[0076] The SEM images of the negative electrodes of the lithium ion batteries of Example 1 and Comparative Example 1 after 400 cycles are as follows: Fig. 9 and Fig.10 As shown, it can be found that after cycling, the surface of the negative electrode of Example 1 is relatively smooth, while the surface of the negative electrode of Comparative Example 1 is uneven, which indicates that a uniform solid electrolyte interface layer can be formed by introducing fluorine-containing and nitrogen-containing polymers, thereby promoting uniform deposition of lithium ions.
[0077] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A gel polymer electrolyte, characterized in that: A polymer framework consisting of the following structure: Among them, R1 is a fluorinated ester group, R2 is -CH3 or -H, and R3 is an amide group.
2. The gel polymer electrolyte according to claim 1, characterized in that: The raw materials of the polymer electrolyte include monomers, crosslinking agents, initiators, organic solvents and lithium salts; the monomers are any one or a combination of two of trifluoroethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, hexafluorobutyl acrylate, 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane and 2-(perfluorohexyl)ethyl methacrylate; the crosslinking agent is one of N,N'-methylenebisacrylamide, hexamethylenebisacrylamide and N,N'-vinylbisacrylamide.
3. The gel polymer electrolyte according to claim 2, characterized in that: The initiator is any one of azobisisobutyronitrile, dicumyl peroxide, dibenzoyl peroxide and azobisisoheptylnitrile.
4. The gel polymer electrolyte according to claim 2, characterized in that: The organic solvent is a mixed organic solvent formed by blending any two or more of ethylene carbonate, diethyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and fluoroethylene carbonate.
5. The gel polymer electrolyte according to claim 2, characterized in that: The lithium salt is any one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, and lithium bis(trifluorosulfonyl)imide.
6. The gel polymer electrolyte according to claim 2, characterized in that: The monomer accounts for 0.1-10 wt % of the electrolyte, the cross-linking agent accounts for 0.1-10 wt % of the electrolyte, and the initiator accounts for 0.001-0.5 wt % of the electrolyte.
7. The gel polymer electrolyte according to any one of claims 2 to 6, characterized in that: The concentration of the lithium salt in the electrolyte is between 0.5 and 2 mol / L.
8. The method for preparing a gel polymer electrolyte according to any one of claims 2 to 7, characterized in that: The precursor electrolyte containing monomers, crosslinking agents, initiators, organic solvents and lithium salts is heated at a temperature of 50 to 80° C. for reaction for 0.5 to 4 hours to convert the precursor electrolyte from a liquid state to a gel state, thereby obtaining the gel polymer electrolyte.
9. Application of a gel polymer electrolyte in a lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the electrolyte is the gel polymer electrolyte according to any one of claims 1 to 7.
10. The use of the gel polymer electrolyte in a lithium ion battery according to claim 9, characterized in that: The positive electrode is one of a nickel-cobalt-manganese ternary positive electrode, a nickel-cobalt-aluminum positive electrode, a lithium cobalt oxide positive electrode, and a lithium iron-manganese phosphate positive electrode; the negative electrode is one of a graphite negative electrode, a lithium titanate negative electrode, a silicon-carbon negative electrode, and a metal lithium negative electrode; the diaphragm is one of a polypropylene diaphragm, a polyethylene diaphragm, a cellulose diaphragm, and a glass fiber diaphragm.
Citation Information
Patent Citations
Phase-change ionic gel, preparation method thereof and ionic device
CN111995771A
Electrolyte for high-voltage polymer lithium battery, lithium battery and preparation method
CN115395093A
4.5 V-resistant gel polymer electrolyte and preparation method thereof
CN117374386A
In-situ polymerization gel polymer electrolyte, preparation method, application and alkali metal battery
CN118073645A
Solid electrolyte based on molecular sieve membrane and solid-state battery
CN118198482A
Cited By
Fluorinated block comb-shaped polymer electrolyte applied to low-temperature lithium metal battery
CN120365477A
Fluorinated phase separation polymer ion gel electrolyte, preparation method and application thereof, and lithium metal battery
CN120854670A
A fluorinated phase-separated polymer ion gel electrolyte, its preparation method and application, and lithium metal batteries.
CN120854670B
Silane coupling agent modified Mxene-based solid-state polymer electrolyte, solid-state lithium battery and preparation method of solid-state lithium battery
CN120999107A
Fluorinated acrylate reference solid electrolyte with hydrogen bond anchoring and amide dissociation as well as preparation method and application of fluorinated acrylate reference solid electrolyte
CN121076238A
